Investigation of the prevalence of carbapenem resistance genes in faecal carriage of carbapenem resistant Klebsiella spp. isolates by multiplex real-time PCR method - Demir, Hatice Kubra; Nakipoglu, Yasar (The Journal of Infection in Developing Countries, 2023)
Introduction: Increased carbapenem resistance in Klebsiella spp. strains causes high morbidity and mortality. The genes encoded for carbapenemaseare transferrable between different bacterial species. In the present study, we aimed to investigate carbapenem resistance genes in Klebsiella spp. strains. Methodology: Fifty Klebsiella spp. strains were isolated from rectal swabs of patients hospitalized in the neonatal intensive care unit (NICU). All strains were identified with API20E. The minimum inhibitory concentrations (MICs) of carbapenems were determined by the broth dilution method. The major five carbapenem genes (OXA-48, NDM, VIM, KPC, and IMP) were detected by the multiplex real-time PCR method. Results: It was found that 49 (98%) of the strains were resistant to ertapenem (MIC ≥ 2μg/mL) and imipenem(MIC ≥ 4 μg/mL), and 47 (94%) of the strains were resistant to doripenem (MIC ≥ 4 μg/mL)and meropenem(MIC ≥ 4 μg/mL).NDM was detected in 42%, OXA-48 in 16%, and VIM in one (2%) isolate, and NDM + OXA-48 co-existed in 36% of the isolates. The KPC and IMP genes were not detected. Conclusions: NDM and NDM co-existing with OXA-48 were prevalent in the NICU of Istanbul Medical Faculty Hospital. Paying attention to the hand hygiene of healthcare workers, screening of rectal swabs of hospitalized patients for the presence of carbapenem resistance strains, and isolation of infected patients can effectively control the spread of carbapenem-resistant strains.